Dominica : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This report describes recent economic developments in Dominica. It highlights that the major trading partners of Dominica are the United Kingdom, the United States, and members of the Caribbean Common Market. Efforts to broaden Dominica's economic base thus far have been met with limited success. Growth in the tourism sector accelerated in the 1990s, but was concentrated on cruise ship passengers because of poor airport access and inadequate hotel capacity. Because of its narrow agricultural base, the economy remains vulnerable to external shocks. The report also describes the public finances and external sector of Dominica.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet